Higuchi's transverse incision and a modification of this method for minimally invasive surgery - Aikou Okamoto; Yoko Nagayoshi; Ayako Kawabata; Masaru Sakamoto; Kazu Ueda (Wolters Kluwer Medknow Publications, 2017)
Study Objective: To describe Higuchi's transverse incision and a modification of this method for reduced port surgery (RPS). Design: Descriptive study. Setting: University hospital. Patients: Those with ovarian cyst and uterine myoma. Intervention: A platform is placed in the 2-3 cm Higuchi incision just above the pubis or on the pubis. Blunt dissection of the subcutaneous adipose tissue is performed. A T incision of the rectus abdominis fascia and a longitudinal incision of the peritoneum are performed. A LAP PROTECTOR and EZ access (Hakko Medical, Nagano, Japan) are used with the platform for single-incision laparoscopic surgery. The peritoneum and fascia are closed by continuous suture, and the skin is closed using the dermostitch technique. Main Results: Higuchi's transverse incision is 2-3 cm in length and is made at a much lower position than the conventional Pfannenstiel transverse incision. The wound is covered by pubic hair, yielding an excellent esthetic outcome. The T incision of the rectus abdominis fascia secures a more extensive surgical field than the Pfannenstiel transverse incision. Conclusion: Higuchi's modified transverse incision ensures a sufficient visual field, yields an excellent esthetic outcome, and is safe, suggesting the potential use of this method for RPS.